From one generation to the next: a comprehensive account of sympathetic receptor control in branching arteriolar trees. (15th July 2015) - Al‐Khazraji, Baraa K.; Saleem, Amani; Goldman, Daniel; Jackson, Dwayne N.
Abstract : Key points: The sympathetic nervous system increases skeletal muscle arteriolar resistance by activating adrenergic, peptidergic and purinergic receptors, which may depend on network topology. To date, there has been limited work conducted on topologically‐dependent sympathetic nervous system control in continuously branching skeletal muscle microvascular networks. In the present study, we investigated how arterioles respond to activation of receptors for sympathetic neurotransmitters based on their location within continuously branching arteriolar trees in skeletal muscle. For the first time, we show differential order‐dependent responses to adrenergic, peptidergic and purinergic agonists in continuously branching arteriolar trees. These results provide novel and detailed network data describing full‐range sympathetic control in the skeletal muscle microcirculation. This work provides much needed experimental data, which can be applied to mathematical models of skeletal muscle blood flow and oxygen transport. Abstract: The effect of the sympathetic nervous system on blood flow distribution within skeletal muscle microvasculature is conditional upon regional activation of receptors for sympathetic neurotransmitters. Previous studies have shown that proximal arterioles are largely governed by adrenergic activation, whereas it is speculated that distal branches are controlled by peptidergic and purinergic activation. However, no study has systematically evaluated the activation of adrenergic, peptidergic and purinergic receptors in continuously branching arteriolar trees of an individual skeletal muscle model. Therefore, in the present study, sympathetic agonists were used to evaluate the constriction responses along first to fifth order arterioles in continuously branching arteriolar trees of a in vivo rat gluteus maximus muscle preparation with respect to specific activation of receptors for sympathetic neurotransmitters (α1R, α2R, NPY1R and P2X1R). Constriction responses were incorporated into a mathematical blood flow model to estimate the total flow, resistance and red blood cell flow heterogeneity within a computationally reconstructed gluteus maximus arteriolar network. For the first time, the effects of activating receptors for sympathetic neurotransmitters on vasoconstrictor responses and the ensuing haemodynamics in continuously branching arteriolar trees of skeletal muscle were characterized, where proximal arterioles responded most to α1R and α2R adrenergic activation, whereas distal arterioles responded most to Y1R and P2X1R activation. Total flow and resistance changed with activation of all receptors, whereas red blood cell flow heterogeneity was largely affected by peptidergic and purinergic activation in distal arterioles. The reported data highlight the functional consequences of topologically‐dependent sympathetic control and may serve as novel input parameters in computational modelling of network flow.